Principales problemas fisiológicos de la mancha anular (Papaya ring spot potyvirus - PRSV) en el cultivo de papaya (Carica papaya L.) - Acosta Murillo, Rene Isaías (2023)
In many tropical and subtropical nations, papaya production is further hampered by papaya ring spot virus, which also causes significant crop losses. Insecticide treatments are not successful due to the mode of transmission of the virus. The objective was to identify ring spot (PRSV) problems in papaya (Carica papaya L.) crops. This document, which has a practical component, will be created by collecting all types of information through research on the different websites, academic works, sources and bibliographic databases available on digital platforms. The findings establish that the symptoms of PRSV-P infection, which were evaluated in this study in greenhouse and field environments, include vein clearance, blade bladder formation, leaf blade loss with only exposed veins, distortion of the blades and petioles, spots on stem and fruits, and plant dwarfism, produces filiform leaves, blisters, thinning of veins, frog legs, mosaic symptoms and systemic chlorosis in indicator plants of Carica papaya "papaya" ; The prevention of aphids with an entomological canopy to the papaya seedbed and the establishment of a barrier with yellow polyethylene plastic and tall grass before transplanting a sprayed insecticide caused late infection of the plants; Similar cases of management decreased the incidence of PRSV. It is considered the main method to control this disease in plants.